طرائق البحوث الكيفية في العلوم الاجتماعية - تواتي إبراهيم, عيسى (My University, 2023)
ازداد مؤخرا الاهتمام بطرق البحث الكيفي نتيجة لكفاءة وفاعلية أساليب المنهج الكيفي المختلفة في جمع وتحليل وتفسير البيانات وصولا إلى تقديم اضافة علمية متميزة. كما أن طبيعة الدراسات في العلوم الاجتماعية والإنسانية تقتضي اختيار الأســـاليب الكيفيـــة التي يتطلـــب معالجتها الحصول علـــى معلومات نوعية لا يمكن توفيرها عن طريـــق اللجوء إلى البحث الكمي. ويعد البحث الكيفي المنهج الأنسب الذي يعبر عن الخصائص المميزة للظاهرة الإنسانية من أجل تحقيق الموضوعية في دراسة السلوك الإنساني. على سبيل المثال فدراسة الحالة، والبحث الاثنوجرافي، والنظرية المجذرة، والبحث الإجرائي، كلها أساليب كيفية تهدف إلى محاولة الحصول عل فهم أعمق للمعاني التي تقف وراء الظاهرة الإنسانية. Abstract: Recently, interest in qualitative research methods has increased as a result of the efficiency and effectiveness of the different qualitative methods in collecting, analyzing and interpreting data in order to provide a distinct scientific addition. Also, the nature of studies in the social and human sciences requires the selection of qualitative methods whose treatment requires obtaining qualitative information that cannot be provided by resorting to quantitative research. The qualitative research is the most appropriate approach that expresses the distinctive characteristics of the human phenomenon in order to achieve objectivity in the study of human behavior. For example, case study, ethnographic research, grounded theory, and action research are all qualitative methods aimed at trying to obtain a deeper understanding of the meanings behind the human phenomenon.
مقال
Keywords: طرق البحث؛ البحث الكيفي ; دراسة الحالة ; الاثنوجرافيا ; النظرية المجذرة ; الظاهراتية ; البحث الاجرائي؛ العلوم الاجتماعية; research methods; qualitative research; Case Study; ethnography; rooted theory; phenomenology; action research; social sciences